Determine the points of maxima and minima of the function $f\left( x \right) = \dfrac{1}{8}\ln x - bx + {x^2},x > 0$, where $b \geqslant 0$ is a constant.
$\left( a \right){\text{min}}{\text{.at }}x = \dfrac{1}{4}\left( {b + \sqrt {{b^2} - 1} } \right),{\text{ max at }}x = \dfrac{1}{4}\left( {b - \sqrt {{b^2} - 1} } \right)$
$\left( b \right){\text{min}}{\text{.at }}x = \dfrac{1}{4}\left( {b - \sqrt {{b^2} - 1} } \right),{\text{ max at }}x = \dfrac{1}{4}\left( {b + \sqrt {{b^2} - 1} } \right)$
$\left( c \right){\text{min}}{\text{.at }}x = \dfrac{1}{4}\left( {b + \sqrt {{b^2} + 1} } \right),{\text{ max at }}x = \dfrac{1}{4}\left( {b - \sqrt {{b^2} - 1} } \right)$
$\left( d \right){\text{min}}{\text{.at }}x = \dfrac{1}{4}\left( {b + \sqrt {{b^2} - 1} } \right),{\text{ max at }}x = \dfrac{1}{4}\left( {b - \sqrt {{b^2} + 1} } \right)$
Answer
Verified
482.4k+ views
Hint: In this particular question to find the maxima and minima differentiate the given function w.r.t x and equate to solve and solve for x, then again differentiate the given function and calculate its value on previous calculated x value if we got positive than it is a minima and if we got negative than it is a maxima so use these concepts to reach the solution of the question.
Complete step by step answer:
Given function.
$f\left( x \right) = \dfrac{1}{8}\ln x - bx + {x^2},x > 0$
Now differentiate this function w.r.t x and equate to zero we have,
$ \Rightarrow \dfrac{d}{{dx}}f\left( x \right) = f'\left( x \right) = \dfrac{d}{{dx}}\left( {\dfrac{1}{8}\ln x - bx + {x^2}} \right) = 0$
Now as we know that $\dfrac{d}{{dx}}\ln x = \dfrac{1}{x},\dfrac{d}{{dx}}{x^n} = n{x^{n - 1}}$, so use this property in the above equation we have,
$ \Rightarrow \left( {\dfrac{1}{{8x}} - b + 2x} \right) = 0$
$ \Rightarrow 1 - 8bx + 16{x^2} = 0$
$ \Rightarrow 16{x^2} - 8bx + 1 = 0$
Now this is a quadratic equation so apply quadratic formula we have,
$ \Rightarrow x = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}$, where a = 16, b = -8b, c = 1
$ \Rightarrow x = \dfrac{{8b \pm \sqrt {{{\left( { - 8b} \right)}^2} - 4\left( {16} \right)} }}{{2\left( {16} \right)}}$
$ \Rightarrow x = \dfrac{{8b \pm \sqrt {64{b^2} - 64} }}{{32}} = \dfrac{{8b \pm 8\sqrt {{b^2} - 1} }}{{32}} = \dfrac{{b \pm \sqrt {{b^2} - 1} }}{4}$
$ \Rightarrow x = \dfrac{{b + \sqrt {{b^2} - 1} }}{4},\dfrac{{b - \sqrt {{b^2} - 1} }}{4}$
So as we see that b should never be less than one other the above values of x will become complex.
Therefore b $ \geqslant $ 1.
Now again differentiate the function w.r.t x we have,
$ \Rightarrow \dfrac{d}{{dx}}f'\left( x \right) = f''\left( x \right) = \dfrac{d}{{dx}}\left( {\dfrac{1}{{8x}} - b + 2x} \right)$
\[ \Rightarrow f''\left( x \right) = \dfrac{d}{{dx}}\left( {\dfrac{{{x^{ - 1}}}}{8} - b + 2x} \right)\]
\[ \Rightarrow f''\left( x \right) = \left( {\dfrac{{ - 1{x^{ - 1 - 1}}}}{8} + 2} \right)\], as the differentiation of constant term is zero.
\[ \Rightarrow f''\left( x \right) = \left( {\dfrac{{ - 1}}{{8{x^2}}} + 2} \right)\]
Now when, $x = \dfrac{{b + \sqrt {{b^2} - 1} }}{4}$ so the value of f” (x) is
\[ \Rightarrow f''\left( x \right) = \dfrac{{ - 1}}{{8{{\left( {\dfrac{{b + \sqrt {{b^2} - 1} }}{4}} \right)}^2}}} + 2\]
Now simplify we have,
\[ \Rightarrow f''\left( x \right) = \dfrac{{ - 16}}{{8{{\left( {b + \sqrt {{b^2} - 1} } \right)}^2}}} + 2\]
\[ \Rightarrow f''\left( x \right) = \dfrac{{ - 2}}{{{{\left( {b + \sqrt {{b^2} - 1} } \right)}^2}}} + 2\]
As b $ \geqslant $ 1 so the value of $\left( {b + \sqrt {{b^2} - 1} } \right)$ when b = 1 is 1
\[ \Rightarrow f''\left( x \right) = \dfrac{{ - 2}}{{{{\left( 1 \right)}^2}}} + 2 = 0\]
So at b = 1 function neither minima nor maxima.
So when, $1 < b < 2$, the value of $\left( {b + \sqrt {{b^2} - 1} } \right) > 1$
\[ \Rightarrow \dfrac{2}{{b + \sqrt {{b^2} - 1} }} = \dfrac{2}{{ > 1}} < 2\]
\[ \Rightarrow f''\left( x \right) = \dfrac{{ - 2}}{{{{\left( {b + \sqrt {{b^2} - 1} } \right)}^2}}} + 2\] = positive.
So when, $x = \dfrac{{b + \sqrt {{b^2} - 1} }}{4}$ the given function is at minimum position.
Now when, $x = \dfrac{{b - \sqrt {{b^2} - 1} }}{4}$ so the value of f” (x) is
\[ \Rightarrow f''\left( x \right) = \dfrac{{ - 1}}{{8{{\left( {\dfrac{{b - \sqrt {{b^2} - 1} }}{4}} \right)}^2}}} + 2\]
Now simplify we have,
\[ \Rightarrow f''\left( x \right) = \dfrac{{ - 16}}{{8{{\left( {b - \sqrt {{b^2} - 1} } \right)}^2}}} + 2\]
\[ \Rightarrow f''\left( x \right) = \dfrac{{ - 2}}{{{{\left( {b - \sqrt {{b^2} - 1} } \right)}^2}}} + 2\]
As b $ \geqslant $ 1 so the value of $\left( {b - \sqrt {{b^2} - 1} } \right)$ when b = 1 is 1
\[ \Rightarrow f''\left( x \right) = \dfrac{{ - 2}}{{{{\left( 1 \right)}^2}}} + 2 = 0\]
So at b = 1 function neither minima nor maxima.
So when, $1 < b < 2$, the value of $\left( {b - \sqrt {{b^2} - 1} } \right) < 1$
\[ \Rightarrow \dfrac{2}{{b - \sqrt {{b^2} - 1} }} = \dfrac{2}{{ < 1}} > 2\]
\[ \Rightarrow f''\left( x \right) = \dfrac{{ - 2}}{{{{\left( {b + \sqrt {{b^2} - 1} } \right)}^2}}} + 2\] = negative.
So when, $x = \dfrac{{b - \sqrt {{b^2} - 1} }}{4}$ the given function is at maximum position.
So this is the required answer.
So, the correct answer is “Option A”.
Note: Whenever we face such types of questions the key concept we have to remember is that always recall the basic differentiation properties such as $\dfrac{d}{{dx}}\ln x = \dfrac{1}{x},\dfrac{d}{{dx}}{x^n} = n{x^{n - 1}}$ so differentiate the given function according to these properties as above.
Complete step by step answer:
Given function.
$f\left( x \right) = \dfrac{1}{8}\ln x - bx + {x^2},x > 0$
Now differentiate this function w.r.t x and equate to zero we have,
$ \Rightarrow \dfrac{d}{{dx}}f\left( x \right) = f'\left( x \right) = \dfrac{d}{{dx}}\left( {\dfrac{1}{8}\ln x - bx + {x^2}} \right) = 0$
Now as we know that $\dfrac{d}{{dx}}\ln x = \dfrac{1}{x},\dfrac{d}{{dx}}{x^n} = n{x^{n - 1}}$, so use this property in the above equation we have,
$ \Rightarrow \left( {\dfrac{1}{{8x}} - b + 2x} \right) = 0$
$ \Rightarrow 1 - 8bx + 16{x^2} = 0$
$ \Rightarrow 16{x^2} - 8bx + 1 = 0$
Now this is a quadratic equation so apply quadratic formula we have,
$ \Rightarrow x = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}$, where a = 16, b = -8b, c = 1
$ \Rightarrow x = \dfrac{{8b \pm \sqrt {{{\left( { - 8b} \right)}^2} - 4\left( {16} \right)} }}{{2\left( {16} \right)}}$
$ \Rightarrow x = \dfrac{{8b \pm \sqrt {64{b^2} - 64} }}{{32}} = \dfrac{{8b \pm 8\sqrt {{b^2} - 1} }}{{32}} = \dfrac{{b \pm \sqrt {{b^2} - 1} }}{4}$
$ \Rightarrow x = \dfrac{{b + \sqrt {{b^2} - 1} }}{4},\dfrac{{b - \sqrt {{b^2} - 1} }}{4}$
So as we see that b should never be less than one other the above values of x will become complex.
Therefore b $ \geqslant $ 1.
Now again differentiate the function w.r.t x we have,
$ \Rightarrow \dfrac{d}{{dx}}f'\left( x \right) = f''\left( x \right) = \dfrac{d}{{dx}}\left( {\dfrac{1}{{8x}} - b + 2x} \right)$
\[ \Rightarrow f''\left( x \right) = \dfrac{d}{{dx}}\left( {\dfrac{{{x^{ - 1}}}}{8} - b + 2x} \right)\]
\[ \Rightarrow f''\left( x \right) = \left( {\dfrac{{ - 1{x^{ - 1 - 1}}}}{8} + 2} \right)\], as the differentiation of constant term is zero.
\[ \Rightarrow f''\left( x \right) = \left( {\dfrac{{ - 1}}{{8{x^2}}} + 2} \right)\]
Now when, $x = \dfrac{{b + \sqrt {{b^2} - 1} }}{4}$ so the value of f” (x) is
\[ \Rightarrow f''\left( x \right) = \dfrac{{ - 1}}{{8{{\left( {\dfrac{{b + \sqrt {{b^2} - 1} }}{4}} \right)}^2}}} + 2\]
Now simplify we have,
\[ \Rightarrow f''\left( x \right) = \dfrac{{ - 16}}{{8{{\left( {b + \sqrt {{b^2} - 1} } \right)}^2}}} + 2\]
\[ \Rightarrow f''\left( x \right) = \dfrac{{ - 2}}{{{{\left( {b + \sqrt {{b^2} - 1} } \right)}^2}}} + 2\]
As b $ \geqslant $ 1 so the value of $\left( {b + \sqrt {{b^2} - 1} } \right)$ when b = 1 is 1
\[ \Rightarrow f''\left( x \right) = \dfrac{{ - 2}}{{{{\left( 1 \right)}^2}}} + 2 = 0\]
So at b = 1 function neither minima nor maxima.
So when, $1 < b < 2$, the value of $\left( {b + \sqrt {{b^2} - 1} } \right) > 1$
\[ \Rightarrow \dfrac{2}{{b + \sqrt {{b^2} - 1} }} = \dfrac{2}{{ > 1}} < 2\]
\[ \Rightarrow f''\left( x \right) = \dfrac{{ - 2}}{{{{\left( {b + \sqrt {{b^2} - 1} } \right)}^2}}} + 2\] = positive.
So when, $x = \dfrac{{b + \sqrt {{b^2} - 1} }}{4}$ the given function is at minimum position.
Now when, $x = \dfrac{{b - \sqrt {{b^2} - 1} }}{4}$ so the value of f” (x) is
\[ \Rightarrow f''\left( x \right) = \dfrac{{ - 1}}{{8{{\left( {\dfrac{{b - \sqrt {{b^2} - 1} }}{4}} \right)}^2}}} + 2\]
Now simplify we have,
\[ \Rightarrow f''\left( x \right) = \dfrac{{ - 16}}{{8{{\left( {b - \sqrt {{b^2} - 1} } \right)}^2}}} + 2\]
\[ \Rightarrow f''\left( x \right) = \dfrac{{ - 2}}{{{{\left( {b - \sqrt {{b^2} - 1} } \right)}^2}}} + 2\]
As b $ \geqslant $ 1 so the value of $\left( {b - \sqrt {{b^2} - 1} } \right)$ when b = 1 is 1
\[ \Rightarrow f''\left( x \right) = \dfrac{{ - 2}}{{{{\left( 1 \right)}^2}}} + 2 = 0\]
So at b = 1 function neither minima nor maxima.
So when, $1 < b < 2$, the value of $\left( {b - \sqrt {{b^2} - 1} } \right) < 1$
\[ \Rightarrow \dfrac{2}{{b - \sqrt {{b^2} - 1} }} = \dfrac{2}{{ < 1}} > 2\]
\[ \Rightarrow f''\left( x \right) = \dfrac{{ - 2}}{{{{\left( {b + \sqrt {{b^2} - 1} } \right)}^2}}} + 2\] = negative.
So when, $x = \dfrac{{b - \sqrt {{b^2} - 1} }}{4}$ the given function is at maximum position.
So this is the required answer.
So, the correct answer is “Option A”.
Note: Whenever we face such types of questions the key concept we have to remember is that always recall the basic differentiation properties such as $\dfrac{d}{{dx}}\ln x = \dfrac{1}{x},\dfrac{d}{{dx}}{x^n} = n{x^{n - 1}}$ so differentiate the given function according to these properties as above.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
The correct order of melting point of 14th group elements class 11 chemistry CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE